2010
DOI: 10.1080/10934529.2010.513290
|View full text |Cite
|
Sign up to set email alerts
|

Surface modified activated carbon with β-cyclodextrin – Part I. Synthesis and characterization

Abstract: Surface functional groups produced from oxidation (carboxylic acid, lactone, quinine, phenol, and nitro groups), reduction (alcohol and amine groups), and grafting (imine and hemi-acetal) reactions were characterized (using surface analysis and chemical methods) and compared with unmodified activated carbon (AC) materials. The untreated, surface-modified, and grafted activated carbon materials were characterized by various surface sensitive methods: Diffuse Reflectance Infrared Fourier Transform Spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The maximum monolayer adsorption capacity of roxarsone ( Q m = 1.783 mmol/g) was achieved with GAC. Although GAC contains a relatively low intrinsic level of Fe content [ 17 ] as an impurity due to its synthetic preparation, the sorptive removal of roxarsone is attributed primarily to noncovalent interactions such π-π stacking and H-bonding between the phenyl ring of roxarsone and the graphene surface of GAC. In the case of composite materials (CM-10, -19, and -32), the Q m value of roxarsone increased as the content of the activated carbon content increased, as anticipated for adsorptive processes influenced by the hydrophobic effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum monolayer adsorption capacity of roxarsone ( Q m = 1.783 mmol/g) was achieved with GAC. Although GAC contains a relatively low intrinsic level of Fe content [ 17 ] as an impurity due to its synthetic preparation, the sorptive removal of roxarsone is attributed primarily to noncovalent interactions such π-π stacking and H-bonding between the phenyl ring of roxarsone and the graphene surface of GAC. In the case of composite materials (CM-10, -19, and -32), the Q m value of roxarsone increased as the content of the activated carbon content increased, as anticipated for adsorptive processes influenced by the hydrophobic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Activated carbon is a microporous amorphous material with relatively high surface areas and surface functional groups with heteroatoms such carbonyl (C=O), hydroxyl (–OH), amino (–NH 2 ), and thiol (–SH), depending on the oxidizing conditions [ 17 ]. These functional groups may serve as electron donors (Lewis base) and may contribute to form metal-pi interactions with metal cations (Lewis acid) on the surface of granular activated carbon (GAC) and on its basal planes.…”
Section: Introductionmentioning
confidence: 99%
“…However, some reports have shown that CDs can be either adsorbed on carbon-based nanomaterials having high surface area and high porosity as activated carbon (AC), 18 immobilized on the surface of carbon-coated cobalt nanomagnets, 19 covalently immovilized at single-walled carbon nanotubes 20 or electrochemically deposited as a film on carbon paste. 21 The grafting of native β-CDs has been also investigated using glutaraldehyde and 1,4-phenylene diisocyanate as organic linker molecules on AC, 22 however, this latter procedure is very time-consuming due to the many hours involved in the various steps of mixing.…”
mentioning
confidence: 99%
“…For instance, the relative concentration of acidic/basic functional groups for biochar is greater than AC due to the presence of more surface polar groups. By contrast AC has reduced surface functionality, as shown by a recent study of these materials (Kwon and Wilson, 2010). The second discriminating feature is the textural properties where AC has a greater BET surface area ($10 3 m 2 /g) compared to the other materials which all are approximately 10 1 m 2 /g (Bismarck et al, 2002;Ayad and Zaghlol, 2012;Sajih et al, 2014;Han et al, 2015).…”
Section: Resultsmentioning
confidence: 94%